Erosion risk mapping: A methodological case study in the Colombian eastern plains - Vrieling, A. (2002)
Soil erosion caused by water is an increasing global problem. Land use and soil conservation planning for large areas requires erosion risk maps, which are typically created using erosion models. These models are often developed for different regions than where they are applied. This paper describes a new qualitative methodology for mapping soil erosion risks over large areas, called Qualitative Erosion Risk Mapping (QUERIM). It is a flexible method that uses decision trees to assign ratings to the erosion-controlling factors. Constructed using expert knowledge, these decision trees reflect the important characteristics influencing erosion risk within a specific region. Ratings for erosion-controlling factors are combined at every location to obtain potential and actual erosion risk maps. QUERIM was applied to the Puerto López municipality in the Colombian Eastern Plains. The obtained erosion risk maps showed agreement with field observations of erosion risk. However, more ground data should be gathered for a better evaluation of the method. It is concluded that a simple qualitative approach such as QUERIM can be more effective in erosion risk mapping than the use of models that were not developed for the region to which they are applied.